Treatment-resistant ophthalmoplegia in Myasthenia gravis: extraocular muscle pathology, the role of TGFβ1 and the derivation of induced pluripotency towards 'disease-in-a-dish' modeling - Rautenbach, Robyn Marié (Department of Medicine, 2017)
Myasthenia gravis (MG) is an autoimmune disease in which pathogenic antibodies target specific neuromuscular junction proteins, most frequently acetylcholine receptors (AChR). Among those without detectable AChR-antibodies, a subgroup of patients has antibodies directed against muscle-specific tyrosine kinase (MuSK). In MG the pathogenic antibodies result in failure of neuromuscular transmission with consequent fatiguable skeletal muscle weakness. MG frequently affects the extraocular muscles (EOMs) early in the course of the disease, resulting in diplopia and ptosis, which is usually reversible with treatment. A treatment-resistant ophthalmoplegia and ptosis occurs as a complication of MG in a distinct subset of cases referred to as OP-MG. The EOMs are highly specialised muscle tissue with a unique physiological and immunological microenvironment with a large satellite cell niche, a distinct muscle fibroblast population, different transcriptional and cellular signaling pathways and fewer intrinsic complement regulatory proteins to protect them against antibody- activated complement-mediated damage. We hypothesised that in OP-MG, there is a differential response of the EOMs to the underlying MG disease process(es) on a genetic and molecular level, resulting in abnormal myofibre homeostasis. We aimed to report descriptive clinical-pathological data pertaining to EOM function and histopathological and ultrastructural EOM tissue analysis of a patient with OP- MG versus that of a non-MG control (both consented to EOM donation at ocular realignment surgery). EOM tissue from an OP-MG individual with AChR- and MuSK- antibody negative MG, demonstrated predominantly myopathic pathology and ultrastructural evidence of mitochondrial stress. The OP-MG EOM findings differ from the control EOM, which showed normal muscle histopathology in a patient undergoing strabismus surgery for a sensory exotropia in a non-seeing eye (loss of retinal stimulus for fusion) and a similar duration of deviation. These OP-MG findings appear to better correlate with previously reported histology/ultrastructure in limb muscle in MuSK-positive MG rather than AChR-positive MG. We next focussed on transforming growth factor beta-1 (TGFβ1) as a critical cytokine involved in muscle repair. An auto-induction pathway in muscle allows TGFβ1 expression to influence the transdifferentiation of satellite cells into myofibroblasts or myoblasts. In orbital fibroblasts, TGFβ1 has also been shown to upregulate decay accelerating factor (DAF), a complement regulatory protein expressed at lower levels in EOMs than other muscles, which should protect against complement-mediated injury. We established OP-MG and control-MG phenotype-specific dermal fibroblast cell lines and performed immunoblotting to evaluate TGFβ1-induced Smad3 phosphorylation and Daf expression in mouse myotubes. We demonstrated repression of phosphorylated-Smad3, a marker of the canonical TGFβ1 pathway, in OP-MG versus control MG fibroblasts after treatment with TGFβ1. We also demonstrated that TGFβ1 significantly upregulates Daf expression levels in mouse myoblasts. Taken together, these results suggest that OP-MG fibroblasts (and possibly myofibroblasts) are likely to be more susceptible to complement-mediated damage and abnormal myofibrogenesis due to their altered response to TGFβ1 stimulation and secondary DAF upregulation. Finally we investigated the feasability of establishing an in vitro disease model for MG or OP-MG by reprogramming dermal fibroblasts into disease phenotype-specific induced pluripotent stem (iPS) cells. We successfully generated and characterised iPS cells for one individual. However, this process was very labour-intensive, cost-inefficient and time-consuming, taking approximately four months to establish pluripotency in a single patient and thereby limited its further application(s). In conclusion, the EOM ultrastructural findings of an OP-MG case are novel and show similar findings to those described in limb skeletal muscle of MuSK-positive MG patients. The TGFβ1 pathway appears to be differentially regulated in OP-MG compared to control-MG cases and this may impact DAF upregulation in the EOMs in MG patients. Finally, our group is exploring an alternative method of establishing a 'disease-in-a-dish' model that is more cost-effective and practically feasible than the iPS cell route.